Cyberpolitics Sebagai Perspektif Baru Memahami Politik di Era Siber [Cyberpolitics as A New Perspective in Understanding Politics in The Cyber Era] - Jerry Indrawan (Jurnal Politica, 2019)
Political science studies have developed from conventional perspectives, marked by the use of physical means of campaign, to the era of non-conventional politics, where the use of cyber medium is more prevalent. The use of cyber medium in the study of political science has resulted in many sectors, from democracy, security, defense, social and cultural affairs, education, to political campaigns to conducted through the cyber medium. Cyberpolitics is a new concept that is very interesting to discuss, as interesting as it is to be studied in detail. Cyberpolitics will be the future of political campaign for all political stakeholders, especially those running in political contests. Political activism has already been replaced by a form of virtual communication. Cyberpolitics can in this regard help democracy work as it should. The aim of this research is to understand cyberpolitics more deeply, and that requires an interdisciplinary perspective, not just political science. The significance of this research is to provide a different perspective to the public about the development of political science, which now moves towards the use of cyber technology. This paper will discuss the study of cyberpolitics, which is seen as a new perspective in understanding politics in the cyber era. The author recommends that studies discussing the concept of cyberpolitics be discussed and researched more intensively among political science scholars, so that the combination of political science and information technology in the future can mutually enrich the scientific understanding of both disciplines.AbstrakKajian ilmu politik sudah berkembang dari yang bersifat konvensional, yaitu menggunakan sarana kampanye yang bersifat fisik, menuju ke era politik non-konvensional, yaitu penggunaan medium siber. Penggunaan medium siber dalam kajian ilmu politik membuat banyak sektor, seperti demokrasi, keamanan, pertahanan, sosial dan budaya, pendidikan, sampai kampanye politik, dilakukan melalui medium siber. Cyberpolitics menjadi sebuah konsep baru yang sangat menarik untuk dibahas, serta diteliti lebih dalam. Cyberpolitics akan menjadi masa depan kampanye politik bagi setiap stake holder politik, terutama bagi mereka yang akan berkontestasi dalam kompetisi pemilihan politik. Aktivisme politik sudah mulai digantikan oleh bentuk komunikasi secara virtual. Cyberpolitics dengan demikian dapat membantu demokrasi berjalan sebagaimana mestinya. Tujuan penelitian ini adalah untuk memahami cyberpolitics secara lebih dalam, sehingga membutuhkan perspektif inter-disipliner, tidak hanya ilmu politik. Kegunaan penelitian ini adalah untuk memberikan perspektif yang berbeda kepada khalayak umum tentang perkembangan ilmu politik, yang sekarang mengarah ke arah penggunaan teknologi siber. Makalah ini akan membahas kajian cyberpolitics, yang dilihat sebagai sebuah perspektif baru dalam memahami politik di era siber. Penulis merekomendasikan bahwa kajian-kajian yang membahas tentang konsep cyberpolitics mulai lebih banyak dibahas dan diteliti di kalangan akademisi-akademisi ilmu politik, agar perpaduan antara ilmu politik dengan teknologi informasi ke depannya dapat semakin memperkaya khazanah keilmuan masing-masing.